2019
DOI: 10.1161/circresaha.118.314515
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SRSF3 in Cardiomyocytes Leads to Decapping of Contraction-Related mRNAs and Severe Systolic Dysfunction

Abstract: Rationale: RBPs (RNA binding proteins) play critical roles in the cell by regulating mRNA transport, splicing, editing, and stability. The RBP SRSF3 (serine/arginine-rich splicing factor 3) is essential for blastocyst formation and for proper liver development and function. However, its role in the heart has not been explored. Objective: To investigate the role of SRSF3 in cardiac function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 50 publications
(63 reference statements)
5
58
1
3
Order By: Relevance
“…PEs regulate SF levels across multiple cell differentiation models, suggesting a post-transcriptional regulatory program that decreases SR protein levels as the tissue differentiates. Our findings also implicate PE splicing in controlling changes in SR protein levels described previously during heart or brain development (Grellscheid et al, 2011;Ortiz-Sá nchez et al, 2019;Roberts et al, 2014;Storbeck et al, 2014). Although we are unable to detect SRSF9-PE splicing in iPSCs, the low levels of PE-containing transcript limit our ability to detect differences in its inclusion and mask its role in cell differentiation.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…PEs regulate SF levels across multiple cell differentiation models, suggesting a post-transcriptional regulatory program that decreases SR protein levels as the tissue differentiates. Our findings also implicate PE splicing in controlling changes in SR protein levels described previously during heart or brain development (Grellscheid et al, 2011;Ortiz-Sá nchez et al, 2019;Roberts et al, 2014;Storbeck et al, 2014). Although we are unable to detect SRSF9-PE splicing in iPSCs, the low levels of PE-containing transcript limit our ability to detect differences in its inclusion and mask its role in cell differentiation.…”
Section: Discussionsupporting
confidence: 48%
“…In all models, most PEs exhibit low inclusion in iPSCs and are more included during differentiation ( Figures 1B-1F, S1A, and S1B). For example, SRSF3-PE inclusion increases in human cardiomyocytes ( Figures 1C and 1D), a pattern that follows the decrease in SRSF3 coding mRNA in embryonic mouse heart development (Ortiz-Sá nchez et al, 2019). TRA2b, critical for brain development (Grellscheid et al, 2011;Roberts et al, 2014;Storbeck et al, 2014), exhibits increased PE inclusion in mature neurons ( Figures 1E and 1F).…”
Section: Sr Protein Pes Are Differentially Spliced During Cellmentioning
confidence: 77%
See 1 more Smart Citation
“…Because of the omnidirectional and multifunctional regulation of mRNA by RBP, even small changes can cause significant physiological and pathological effects. Previous studies have indicated that cancer, neurodegenerative diseases, and cardiovascular diseases have been proven to be associated with RBP abnormalities [ 2 , 31 , 42 ]. Cell proliferation, differentiation, apoptosis, and other physiological processes are precisely regulated at the post-transcriptional level, which is involved in the development of tumors [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…SRSF3 plays a critical role in the regulation of RNA splicing and many other cellular functions. Aberrant SRSF3 function can be identified in several human diseases, including Alzheimer's disease ( 7 ), systolic heart failure ( 8 ), ocular hypertension ( 9 ), virus infection ( 10 12 ), and tumor ( 13 ). In this review, we summarize current research on the function and expression regulation of SRSF3 and the misregulation and biological implications of SRSF3 in cancer, as well as its therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%